Auditoria en Seguridad Vial Vía Armenia-Pereira, Km 15+600 al Km 21+600 (2023)
Road safety audits are essential for identifying and assessing the risk factors that impact both road infrastructure and its users. They represent a methodical process that spans the planning, construction, and implementation phases of a road, enabling the anticipation of potential issues and the implementation of preventative and corrective measures to ensure the safety of road users. In this project, a road safety audit was conducted on the Armenia-Pereira road section spanning kilometers 15+600 to 21+600.